2007
DOI: 10.1111/j.1747-0765.2007.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Humus composition of Amazonian Dark Earths in the Middle Amazon, Brazil

Abstract: The process of humus accumulation has been one of the most important aspects in the pedogenesis of Amazonian Dark Earths (ADE) and Terra Mulata (TM). ADE has been characterized by higher contents of P, Ca and humus than adjacent Yellow Latosol (YL) under anthropogenic effects, and TM has been characterized by slightly less dark topsoil than ADE. The objective of this study was to analyze the composition of humus in ADE using the Kumada's method. A total of 20 soil samples of the A horizons and the transitional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…This suggests that the presence of HAs associated with Ca was larger than with Fe and Al. HAs extracted with Na 4 P 2 O 7 revealed a stronger association with Fe and Al than with Ca (e.g., Nakamura et al 2007). As described in Section 3.1, the soils in this study were Ca-enriched.…”
Section: Forms Of Has Present In the Soilsupporting
confidence: 56%
See 2 more Smart Citations
“…This suggests that the presence of HAs associated with Ca was larger than with Fe and Al. HAs extracted with Na 4 P 2 O 7 revealed a stronger association with Fe and Al than with Ca (e.g., Nakamura et al 2007). As described in Section 3.1, the soils in this study were Ca-enriched.…”
Section: Forms Of Has Present In the Soilsupporting
confidence: 56%
“…Type A-HA is commonly observed in the A horizon of Japanese Andosols derived from volcanic ash and charred materials could be an important source (Tate et al 1990;Shindo et al 2004;Nishimura et al 2009). However, in the A horizon of Chernozemic soils, charred organic C was also observed in Europe (Schmidt et al 1999), which contributes to C storage and the formation of Type A-HA, similar to the humus accumulation in Japanese Andosols (Nishimura et al 2009).…”
Section: Optical Characteristics Of Hasmentioning
confidence: 95%
See 1 more Smart Citation
“…[52,53] It is also possible that HAC-P (com- bined form C) adsorbed less 2,4-D than HAC-OH (free form C) because combined form C is in closer contact with clay minerals than free form C. [8,9] For example, a previous study reported that the presence of highly (negatively) charged clay minerals reduces the importance of metalhumate complexes as sorbents of 2,4-D. [44] Several researchers have suggested that sorptionpartition coefficients such as Koc can be calculated using the structural characteristics of SOM. [54,55] In the current study, Koc was significantly positively correlated with the ε 280 of HA-OH, suggesting that the capacity of SOM to retain 2,4-D increased with increasing HA-OH aromaticity [9,56] and hence the abundances of conjugated C=C bonds. [7] The CPMAS 13 C-NMR on whole soils indicated that the O-alkyl C region dominated the C pool in all soil samples, which is in agreement with that observed for a wide range of soils in Australia and Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] HS can be fractionated by sequential extractions with sodium hydroxide (NaOH) followed by sodium pyrophosphate (Na 4 P 2 O 7 ). [7] HAs and FAs extracted by NaOH represent the fractions present as free form C. [7] HAs and FAs that are not extractable by NaOH but can be extracted by Na 4 P 2 O 7 are considered to be the combined form C fractions [7] and in closer contact with clay minerals than free form C. [8,9] Piccolo et al [10] demonstrated that NaOH-extracted HS have a greater sorption capacity for atrazine (a weakly-basic herbicide) than Na 4 P 2 O 7 -extracted HS.…”
Section: Introductionmentioning
confidence: 99%